Crystal Mangum as Hypervisible Object and Invisible Subject: Black Feminist Thought, Sexual Violence, and the Pedagogical Repercussions of the Duke Lacrosse Rape Case - Phillips, Joshua Daniel; Griffin, Rachel Alicia (Women's studies in communication, 2015)
In March 2006 Crystal Mangum, a Black female exotic dancer, accused three White male Duke student-athletes of sexual violence, igniting a firestorm of media coverage. This article focuses on the public treatment of Mangum, before and after the case was legally resolved, illustrating how she became hypervisible as a vilified object and invisible as a credible subject. Drawing on Black feminist thought, we consider how representations of Mangum serve pedagogical functions, teaching Black female survivors to stay silent.